Pulmonary function in patients with ANCA-associated vasculitis - Dieterich, Johannes; Hellmich, Bernhard; Mahrhold, Juliane; Feng, You-Shan; El Rai, Abdallah; Nessyt, Felix; Specks, Ulrich; Hetzel, Jürgen; Löffler, Christian (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Although pulmonary manifestations occur frequently in ANCA-associated vasculitis (AAV), empirical evidence of their impact on pulmonary function is scarce. This study analyzed pulmonary function test (PFT) data from a large cohort of patients with AVV. Results were correlated with findings from diagnostic imaging and disease activity. Methods: Data from AAV patients with PFTs performed between 2008 and 2018 were extracted retrospectively from the database of a tertiary vasculitis center. Demographic and disease characteristics, imaging data and follow-up results were assessed and compared to PFT results. Results: The final analysis encompassed 147 patients. The mean time between first PFT and follow-up was 7.0 ± 11.0 months. In Granulomatosis with Polyangiitis (GPA), forced expiratory vital capacity (FVCex, p